GENDER LANGUAGE CHARACTERISTICS USED BY STUDENTS IN BOARDING HOUSE - Herois T. Simaremare; Amrin Saragih; Sri Minda Murni (LINGUISTIK TERAPAN, 2018)
The study deals with the gender language characteristics used by students in boarding house. This study attempted to find out the gender language characteristics used by students and to describe the reason why are the gender language characteristics used by students in boarding house. This study was conducted by using qualitative design. The data in this study were taken from the recorded utterancesof the students in boarding house and interview. The source of data were four male and four female students. The utterances were recorded and transcribed in order to be analyzed. The data were analyzed by using interactive model by Miles, Huberman and Saldana (2014). The findings showthat all the male language characteristics used by male and female students in boarding house. While, not all female language characteristics used by them, the male students used 7 kinds of female language characteristics and the female students used 8 kinds of female language characteristics. The most dominantly of male language characteristics used by gender students is judgement adjectives, while the most dominantly of female language characteristics is taq questions. Meanwhile, there were four reasons that affect the using of language characteristics used by students in boarding house.Keywords:  Gender Language, Male Language Characteristics, Female Language Characteristics, Utterances